W. Ross Silcock letter to Thomas H. Kent regarding bird sightings, May 31, 1980 - Silcock, W. Rosset al (1980)
Field notes contributed by W. Ross Silcock in a letter to Thomas H. Kent, May 31, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed